The Examination of Teachers’ Views on Metaverse-Based Education - Sağ, Mert; Semerci, Nuriye; Özçelik, Ceyda (Journal of Interdisciplinary Studies in Education, 2024)
The aim of this study is to determine teachers’ views on metaverse-based education. The research is a qualitative study and was conducted with a phenomenological design. In the study, maximum diversity sampling technique, one of the purposeful sampling methods of the study group, was used. In this direction, data were collected from as many different teachers as possible, taking into account their age, field of study, school type and gender. The research was carried out with 32 teachers. The data were collected through face-to-face interviews using a semi-structured interview form consisting of four questions about personal information and 11 questions about the metaverse. The data were analysed by descriptive analysis method using MAXQDA software. Teachers stated that as a result of the integration of metaverse technology into education and training processes, education and training processes will become quality, efficient and more permanent.